2004
DOI: 10.1152/jn.00301.2004
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Inhibition for Center-Surround Reorganization of the Frequency Map of Bat Auditory Cortex

Abstract: Ma, Xiaofeng and Nobuo Suga. Lateral inhibition for center-surround reorganization of the frequency map of bat auditory cortex. J Neurophysiol 92: 3192-3199, 2004; doi:10.1152/jn.00301.2004. Repetitive acoustic stimulation, auditory fear conditioning, and focal electric stimulation of the auditory cortex (AC) each evoke the reorganization of the central auditory system. Our current study of the big brown bat indicates that focal electric stimulation of the AC evokes center-surround reorganization of the freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…As shown in the present paper, electric stimulation accompanied with ACh applied to the AC evoked the long-term plastic change (BF shift) in the AC, as auditory fear conditioning does. This finding and others (3,4,11,12) indicate that the short-term cortical BF shift is evoked by the neural circuit intrinsic to the AC and corticofugal feedback system and is augmented by the cholinergic basal forebrain, as hypothesized by Gao and Suga (2). However, there are several intriguing problems to be solved.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…As shown in the present paper, electric stimulation accompanied with ACh applied to the AC evoked the long-term plastic change (BF shift) in the AC, as auditory fear conditioning does. This finding and others (3,4,11,12) indicate that the short-term cortical BF shift is evoked by the neural circuit intrinsic to the AC and corticofugal feedback system and is augmented by the cholinergic basal forebrain, as hypothesized by Gao and Suga (2). However, there are several intriguing problems to be solved.…”
Section: Discussionsupporting
confidence: 65%
“…3-5. Focal electric stimulation of the AC (ES a ) evokes BF shifts of cortical and collicular neurons (9,(22)(23)(24)(25). ACh applied to the AC without conditioning or cortical electric stimulation evokes neither cortical nor collicular BF shifts, but it augments BF shifts evoked by conditioning (4) or cortical electric stimulation (12). In Fig.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…However, we may speculate the mechanism for the serotonergic modulation. The direction of the BF shift depends on the balance between excitation and inhibition occurring in the AI, because muscimol (an agonist of GABA A receptors) changes the centripetal BF shift into a centrifugal BF shift (Ma and Suga, 2004), and bicucullin (an antagonist of GABA A receptors) changes the centrifugal BF shift into a centripetal BF shift (Xiao and Suga, 2002;Ma and Suga, 2004). Ritanserin (a 5-HT 2A receptor antagonist) suppressed the cortical auditory response and changed the centripetal BF shift into a centrifugal BF shift.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that pyramidal cell tuning in the visual and auditory systems depends on a balance of thalamocortical excitatory inputs and local circuit inhibition (Wehr and Zador, 2003;Ma and Suga, 2004). For example, in the visual cortex (V1), narrow orientation tuning is generated by both an enhancement near the preferred orientation caused by specific inputs from the LGN and corticocortical amplification, and by global suppression supplied by cortical inhibition (Ferster and Miller, 2000;Shapley et al, 2003).…”
Section: Introductionmentioning
confidence: 99%